Critical Pedagogy in TESL/TEFL: How Far Can We Go? - Yumarnamto, Mateus (Beyond Words, 2013)
In this post-method era, perspectives and stances gain momentum as postmodernist’ educators highlight teachers’ agency in transforming the students and the society. In this framework, this paper discusses two approaches in teaching English as a second or foreign language (TESL/TEFL). The first perspective is critical pedagogy and the second is pragmatic pedagogy. By discussing the two important perspectives, this paper aims at understanding the path for better practices, both in research and teaching in TESL/TEFL. More importantly, it also discusses its relevance to teaching English in Indonesian.